A Review on the Thermal Modeling Method for Molten Salt Receivers of Concentrating Solar Power Tower Plants - Xinyi Li; Fengwu Bai (Energies)
Concentrating solar power (CSP) tower plants using molten salt as the heat transfer fluid are currently the predominant technology used globally, and have experienced rapid development in recent years. The molten salt receiver, as the core piece of equipment for converting solar energy into thermal energy, directly determines the system efficiency, while its safety affects the plant’s operating hours. This paper reviews the details and operational status of commercial-scale CSP tower plants worldwide as of the end of 2023. It systematically summarizes the typical thermal models for mainstream tubular molten salt receivers by reviewing 37 models, including 11 three-dimensional (3D) numerical models, 8 two-dimensional (2D) semi-empirical models, and 18 one-dimensional (1D) semi-empirical models. By comparing and analyzing the key features of each model, the study concludes that detailed 3D numerical models are effective for monitoring overheating during operation, 2D semi-empirical models enable the rapid evaluation of receiver configurations, and 1D semi-empirical models support transient mass flow calculations and annual power generation estimations. Additionally, the paper outlines the current applications of receiver thermal models in system integration, particularly in combining CSP tower systems with other energy systems.